Evaluating chemical properties and sustainable recycling of waste foundry sand in construction materials - Chifflard, Peter; Schütz, Michaela; Reiss, Martin; Foroushani, Mansour Ahmadi (Frontiers in Built Environment, 2024)
Waste Foundry Sand (WFS) is a byproduct from metal casting processes, often contaminated with heavy metals, acids, and carbon residues. As disposal costs rise, there is growing interest in repurposing WFS as an alternative to traditional aggregates in construction materials such as bricks, tiles, and concrete. However, concerns about the potential leaching of harmful chemicals into soil and groundwater pose significant barriers to its widespread use. By reducing the chemical pollutants, WFS becomes a competitive option for sustainable construction materials. This study aims to address these concerns by developing methods to extract WFS from the production cycle before it exceeds regulatory limits, thereby enhancing its suitability for recycling and reducing disposal costs. We assessed waste foundry sand (WFS) samples from various production cycles, following permissible guidelines, by mixing them with cement in proportions of 1%, 3%, and 5%. Our evaluation focused on their effectiveness as construction materials. The results indicated that the sample with 1% cement slightly exceeded the permissible limits for polycyclic aromatic hydrocarbons (PAHs), whereas the samples with 3% and 5% cement content complied with all regulatory standards. These findings suggest that WFS, particularly when combined with higher cement contents, holds promise as a sustainable construction material. This method not only reduces the need for extensive treatment and reclamation processes but also presents a cost-effective and environmentally friendly approach to managing WFS.